Extractability of soluble protein from different types of skeletal muscles in cattle under the treatment of pH, molarity and type of buffers - M. Z., Noor Azihan; Sazili, Awis Qurni; Mustafa, Shuhaimi; Abdullah, Muhammad Hilmi; Panandam, Jothi Malar (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Soluble protein can be extracted if muscle fibres are lysed and the extractability depends on several factors such as choice of buffer, presence of protein inhibitor and the osmolarity of the resuspension buffer (1). Proteins can be severely affected by small changes in hydrogen ion concentration. Some proteins tend to precipitate when the pH approaches their isoelectric point (pI) (7). Therefore, in order to ensure reproducible results, it is important to maintain the protein solution at the constant pH. Once an optimal pH has been determined, different buffer within the same pH range may also be examined for specific buffer effects (2). Different types of skeletal muscles are composed of different proportion of fibers at which the differences influence the metabolic capability (4, 6). Differences in rate of post-mortem glycolysis could induce changes in protein solubility (3). In addition, the selection of the ST, LD and SS muscles for the study was based on their previously reported metabolite and contractile characteristic as well as fiber type composition (5). The aim of this study was to evaluate the effects of the type, pH and molarity of extraction buffer on protein extractability from beef Semitendinosus (ST) Longissimus dorsi (LD) and Supraspinatus (SS) muscles.